Tenosynovial Giant Cell Tumors of the Hand: Analysis of Risk Factors for Surgical Margin and Recurrence - Tolgahan Cengiz; Şafak Aydın Şimşek; Ercan Bayar; Furkan Erdoğan; Alparslan Yurtbay; Hüseyin Sina Coşkun; Ahmet Pişkin; Nevzat Dabak (Medicina, 2025)
Background and Objective: Tenosynovial giant cell tumors (TGCTs) are benign but potentially aggressive soft-tissue tumors, most commonly affecting the hand and frequently associated with local recurrence despite surgical treatment. While positive surgical margins are recognized as the strongest predictor of recurrence, the preoperative identification of factors influencing margin status remains underexplored. This study analyzed the risk factors associated with surgical margin positivity and local recurrence in patients treated for localized hand TGCTs, contributing to more accurate preoperative risk stratification. Materials and Methods: A retrospective analysis was conducted on 44 patients diagnosed with localized TGCTs of the hand and treated surgically at a tertiary regional hospital between 2009 and 2023. Demographic characteristics, tumor size and location, anatomical relationships (bone, joint, and neurovascular proximity), Al Qattan classification, and surgical outcomes were recorded. Binary logistic regression was used to evaluate the impact of these variables on surgical margin status and recurrence. Postoperative satisfaction was assessed using a four-choice questionnaire. Results: The mean patient age was 47.5 years, with 68.2% being female. The most common tumor site was the second finger (31.8%), and 20.5% of patients had positive surgical margins. Recurrence occurred in four patients (9.1%). Bone invasion, interphalangeal joint proximity, neurovascular involvement, and Al Qattan type 2 tumors were statistically significant risk factors for both surgical margin positivity and recurrence. Lesions with periosteal involvement, however, did not significantly impact recurrence risk. Among patients with positive margins, 44.4% developed recurrence. Conclusions: Complete surgical excision with clean margins remains the cornerstone of TGCT management. This study uniquely identifies preoperative predictors of margin positivity—key contributors to recurrence—highlighting the importance of meticulous surgical planning in high-risk cases. Close postoperative follow-up is essential, particularly for patients with positive margins, to detect and manage recurrence promptly.